The Influence of Professional Engineering Organizations on Women and Underrepresented Minority Students’ Fit - Campbell-Montalvo, Rebecca; Kersaint, Gladis; Smith, Chrystal A. S.; Puccia, Ellen; Sidorova, Oxana; Cooke, Hannah; Wao, Hesborn; Martin, Julie P.; Skvoretz, John; MacDonald, George; Lee, Reginald (Frontiers in Education, 2022)
Our work focuses on women and underrepresented minority (URM) students’ cultural models of engineering success (CMES) or beliefs about doing well in engineering. Because of its consequential effect on persistence, we pay special attention to the fit domain of CMES—student feelings of belonging in their engineering program. We examine 1) how student fit is affected by participatory social capital (i.e., participation in professional engineering organizations [PEOs]) that have as part of their mission a goal to assist students in their STEM education and careers, as well as 2) the factors that affect students’ decisions to participate in PEOs. Due to the traditional prioritization of majority norms in engineering programs, women and URM students’ CMES may conflict with the cultures manifested in engineering departments. Analysis of interviews with 55 women and URM engineering students shows that PEOs, particularly gender- and race-focused PEOs, affect students feelings of fit positively and primarily through expressive social capital—emotional support wherein students feel they fit in because PEOs provide a sense of community and opportunities to be around successful women and URM engineers. PEOs also allow students to build instrumental social capital, such as academic and professional skills, including networking and knowledge development. Encouragement from others and their desire to be around people like themselves played a central role in students joining PEOs. However, students identified time, financial, and fit issues that discouraged them from participating in PEOs. Research, theory, and practice applications are presented.